2009
DOI: 10.1103/physreva.79.013408
|View full text |Cite
|
Sign up to set email alerts
|

Optimal geometry for efficient loading of an optical dipole trap

Abstract: One important factor which determines efficiency of loading cold atoms into an optical dipole trap from a magneto-optical trap is the distance between the trap centers. By studying this efficiency for various optical trap depths (2--110 mK) we find that for optimum dipole trap loading, longitudinal displacements up to 15 mm are necessary. An explanation for this observation is presented and compared with other work and a simple analytical formula is derived for the optimum distance between the trap centers.Com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…7. It has been pointed out earlier [15] that the potential surface is an ellipsoidal surface with larger area away from focal position. Kuppens et al [6] suggested that initial loading rate of ODT is proportional to the effective surface area of ODT.…”
Section: B Effective Absorption Cross-section and Optical Densitymentioning
confidence: 90%
See 2 more Smart Citations
“…7. It has been pointed out earlier [15] that the potential surface is an ellipsoidal surface with larger area away from focal position. Kuppens et al [6] suggested that initial loading rate of ODT is proportional to the effective surface area of ODT.…”
Section: B Effective Absorption Cross-section and Optical Densitymentioning
confidence: 90%
“…Kuppens et al [6] suggested that initial loading rate of ODT is proportional to the effective surface area of ODT. In view of this, it can be beneficial for ODT loading to align dipole trap beam on the MOT such that MOT position was slightly shifted from focal position of the ODT beam [15]. In order to correctly estimate the number atoms (N) trapped in ODT, the effective absorption cross-section σ ef f calculated after knowing position and intensity dependent AC-Stark shift has been used in the analysis of experimentally observed absorption images of the trapped atom cloud.…”
Section: B Effective Absorption Cross-section and Optical Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The applications of the researches in the FORT mainly involve the use of the dipole forces, called as optical dipole force trap. Moreover, although the near-optical resonant trap (NORT), which has a small detuning round of several tens of GHz to several THz, has been treated with * Electronic address: tojo@phys.chuo-u.ac.jp experimental difficulties because of heating, scattering, and dephasing beyond their perturbative conditions by the spontaneous emission [16,17], there is a possibility of using not only the dipole force but also the radiative force as the hybrid force trap.…”
Section: Introductionmentioning
confidence: 99%
“…Chapman et al managed to condense 87 Rb in a dipole trap consisting of two crossed CO 2 laser beams by means of evaporative cooling [17] and all-optical crossed-beam setups have also enabled the first observation of Bose-Einstein condensation of cesium and ytterbium atoms [18,19]. Optical traps consisting of one single focused laser beam were used to produce degenerate Fermi gases [20] and Fermi gas mixtures [21] and to achieve condensation of 87 Rb [23], and they are a popular way to trap and store cold gases for multiple needs [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%